Coexisting schwannoma of the gallbladder and sarcoidosis: a case report - Takuya Tajiri; Hiromitsu Hayashi; Takaaki Higashi; Takanobu Yamao; Toru Takematsu; Norio Uemura; Kensuke Yamamura; Katsunori Imai; Yo-ichi Yamashita; Hideo Baba (Surgical Case Reports)
Abstract Background Schwannomas originate from Schwann cells, which are constituents of peripheral nerve sheaths, and can occur anywhere in the body at any age. Most occur in soft tissues such as subcutaneous tissues and muscles, occurrence in the abdominal cavity being relatively rare. In particular, schwannomas of the gallbladder are extremely rare. We herein report a rare case of a schwannoma that coexisted with systemic sarcoidosis and presented as a steroid-resistant mass in the gallbladder wall. Case presentation A 40-year-old woman was found to have thickening of the gallbladder wall during a routine medical examination and was referred to our hospital, where she was found to have granular shadows in the lungs; mediastinal, cervical, intraperitoneal, and inguinal lymphadenopathy; parotid gland enlargement; and an erythematous skin rash. She was diagnosed as having systemic sarcoidosis by transbronchial lung biopsy and bronchoalveolar lavage. All her systemic mass lesions except for the one in the gallbladder resolved or became smaller with steroid treatment. The steroid-resistant gallbladder lesion showed enhancement on contrast-enhanced computed tomography and was shown by endoscopic ultrasonography to be a 30-mm-diameter gallbladder wall lesion. We performed laparoscopic cholecystectomy, which resulted in diagnosis of the steroid-resistant tumor as a schwannoma. Five months after surgery, the patient’s prednisolone dosage had been gradually reduced to 5 mg/day and she was doing well with no evidence of recurrence. Conclusion Resection of a steroid-resistant tumor resulted in diagnosis of schwannoma, enabling reduction in the patient’s steroid dosage for sarcoidosis.